Norm Values of Head Circumference in Turkish Children - Haluk Yavuz; M. Akif Bakır; Saime Sündüs Uygun (Genel Tıp Dergisi)
Objective: Measuring head circumference is a quick, simple, cheap, noninvasive and reliable procedure for determining underlying brain size and provides information about risk for medical problems. Growth percentages of head vary from one community to another. Methods: We aim to create head circumference growth curves for children aged 0-18 years in Turkish community. Measurements were performed by same person using a rigid and calibrated tape meter. In addition, the parents were asked to fill out a questionnaire with variables that could affect children's growth. Results: Data analysis has shown that there is no relationship between the children's head circumference and whether there exists someone with a large/small head circumference in their families, or the average monthly income of their families and the parent’s education level. Only the independent variables child’s school performance, birth weight, nutrition, smoking are significantly effective on the HC measures of boys at alpha=0.05 level. For girls, only the independent variables birth weight and nutrition form are significantly important in explaining the variability of HC at the level of alpha=0.05. One gram increase in birth weight causes a 0.001 cm increase in the HC of both genders. In addition, head circumference growth curves were created for both genders to include all children aged 0-18. Conclusions: Our study offers recent and gender-specific head circumference norms. These new values can be used more effectively in child follow-up.